Analysis of poisoning with OTC drugs for suicidal purposes among children and adolescents in Poland in the period 2012 - 2023 - Maria Kubicka; Paulina Polańska; Marta Gruszka; Martyna Zakrocka (Journal of Education, Health and Sport)
Introduction and Purpose: Drug poisoning among children and adolescents is an increasing public health issue worldwide and in Poland. Intentional poisonings, especially suicide attempts, are on the rise, often involving over-the-counter (OTC) medications, with paracetamol being the most commonly used substance. This paper aims to analyze the prevalence, characteristics, and implications of drug poisonings in youth, focusing on social and mental health factors, particularly during the COVID-19 pandemic.